2015
DOI: 10.1186/s13068-015-0358-0
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic analysis of the deacetylation and disk refining process: characterizing the effect of refining energy and enzyme usage on minimum sugar selling price and minimum ethanol selling price

Abstract: BackgroundA novel, highly efficient deacetylation and disk refining (DDR) process to liberate fermentable sugars from biomass was recently developed at the National Renewable Energy Laboratory (NREL). The DDR process consists of a mild, dilute alkaline deacetylation step followed by low-energy-consumption disk refining. The DDR corn stover substrates achieved high process sugar conversion yields, at low to modest enzyme loadings, and also produced high sugar concentration syrups at high initial insoluble solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 8 publications
1
57
0
Order By: Relevance
“…In our previous work, the TEA analysis showed refining energies over 200 kWh/ODMT will require a bioethanol plant to purchase electricity from the grid due to the high energy demand. 13 External energy input not only increases the sugar and final product costs, but also increases the greenhouse gas emissions. In addition, refining energy could also affect the biomass digestibility.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous work, the TEA analysis showed refining energies over 200 kWh/ODMT will require a bioethanol plant to purchase electricity from the grid due to the high energy demand. 13 External energy input not only increases the sugar and final product costs, but also increases the greenhouse gas emissions. In addition, refining energy could also affect the biomass digestibility.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous TEA work revealed that enzyme loading at 20 mg total protein per gram of cellulose (14 FPU or 0.074 mL CTec3 product/g of cellulose) may not be economic because of the large tank volume needed and the associated high cost for air. 13 Therefore, we investigated the multistage SM-DRDCS process for potential reductions in enzyme loading. Figure 5 shows the enzymatic sugar yields using the SM-DRDCS-1 substrate at cellulase/hemicellulase enzyme loadings of 5, 10, 15, and 20 mg of total protein per gram of cellulose in the refined residues.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pretreatment and hydrolysis expenditure accounts for 20% of the total capital and operating costs of biorefining and is only eclipsed by material and feedstock costs . Low‐cost sugar production is regarded as the primary driver for the use of biomass feedstocks to produce biofuels and other biobased chemicals, such as furfural, 5‐HMF, and levulinic acid, in the biorefining industry …”
Section: Introductionmentioning
confidence: 99%